CYTOKINE PROFILE OF TH1- AND TH2-DEPENDENT VARIANTS OF CHRONIC GVHD - O. T. Kudaeva; V. O. Tkachev; E. D. Gavrilova; E. V. Goiman; N. N. Volsky; O. M. Perminova; O. P. Kolesnikova (Медицинская иммунология, 2014)
Abstract. Induction of chronic GVHD in the DBA/2→(C57Bl/6xDBA/2) F1 semi-allogeneic murine model results into development of Th1- and Th2-dependent immunopathological conditions that are characterized by different cytokine profiles. Chronic GVHD is accompanied by a sharp increase in IgE levels, thus presuming considerable IL-4 production. In recipients with Th2-dependent GvHD variant, elevated contents of serum IL-6, IL-7 and TNFα were also observed, which, along with other effects, may support polyclonal activation of B cells, thus leading to development of autoimmune pathology.